Nigeria : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Nigeria. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that the Nigerian economy is exiting recession but remains vulnerable. New foreign exchange measures, rising oil prices, attractive yields on government securities, and a tighter monetary policy have contributed to better foreign exchange availability, increased reserves to a four-year high, and contained inflationary pressures. Economic growth reached 0.8 percent in 2017, driven mainly by recovering oil production. Inflation declined to 15.4 percent year-over-year by end-December, from 18.5 percent at end-2016. Higher oil prices are supporting the near-term projections, but medium-term projections indicate that growth would remain relatively flat, with continuing declines in per capita real GDP under unchanged policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet